Beyond the Binary: Sexual and Reproductive Health Considerations for Transgender and Gender Expansive Adolescents - Lunde, Claire E.; Spigel, Rebecca; Gordon, Catherine M.; Sieberg, Christine B. (Frontiers in Reproductive Health, 2021)
Awareness and visibility of transgender individuals have grown exponentially. However, conceptualizing sexual and reproductive health (SRH) as “women’s” or “men’s” health services further marginalizes transgender and gender-expansive (TGE) youth. Multiple reviews and commentaries have been published on the topic of SRH care for adults under the umbrella term of sexual and gender minorities, all with a call to action for more inclusive care and the need for more clinical research involving TGE individuals, and notably, TGE youth. Results from adult TGE studies are often translated to describe adolescent models. However, models specific to adolescent TGE populations are needed to understand their unique SRH needs. This review will describe the current literature relating to SRH needs of TGE youth and adults, highlighting key areas with significant disparities in need of further research. This comprehensive summary will also provide recommendations for clinicians and researchers with the goal of improving SRH care and obtaining wider representation in both clinical settings and research directed toward TGE youth.